2018
DOI: 10.1021/acs.chemmater.8b03331
|View full text |Cite
|
Sign up to set email alerts
|

Achieving Highly Stable, Reversibly Reconfigurable Plasmonic Nanocrystal Superlattices through the Use of Semifluorinated Surface Ligands

Abstract: Controlling stability, complexity and optical response of reversibly reconfigurable plasmonic nanocrystal superlattices is of critical importance for emergent optoelectronic technologies and can be achieved by engineering the chemical nature of the ligand shell. In this work, we experimentally explore how the design of surface ligands with semifluorinated alkyl chains impacts dynamic self-assembly of nanoparticles. A series of three promesogenic thiols was synthesized and grafted onto plasmonic nanocrystals vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
30
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 12 publications
(33 citation statements)
references
References 67 publications
3
30
0
Order By: Relevance
“…These were indexed as (002), (011), (004), and a pair of (013) and (110) signals, assuming a tetragonal body-centered unit cell with unit cell parameters c ≈ 12.8 nm and a ≈ 4.2 nm. These observations were in agreement with the already shown tendency of liquid-crystalline-like ligand coated NPs to adopt this symmetry [27,36,42] as well as interparticle spacing. Surface-to-surface distance of neighbor NPs is~0.9 nm along the a direction, and 3.7 nm, along the unit cell diagonal direction.…”
Section: Thermally Driven Self-assembly Of Nanoparticlessupporting
confidence: 92%
See 2 more Smart Citations
“…These were indexed as (002), (011), (004), and a pair of (013) and (110) signals, assuming a tetragonal body-centered unit cell with unit cell parameters c ≈ 12.8 nm and a ≈ 4.2 nm. These observations were in agreement with the already shown tendency of liquid-crystalline-like ligand coated NPs to adopt this symmetry [27,36,42] as well as interparticle spacing. Surface-to-surface distance of neighbor NPs is~0.9 nm along the a direction, and 3.7 nm, along the unit cell diagonal direction.…”
Section: Thermally Driven Self-assembly Of Nanoparticlessupporting
confidence: 92%
“…The phase sequences of such materials and their structural parameters are strictly dependent on the interplay between the nanoparticle core and the structure of ligands. Several hybrid materials, reconfigurable between ordered lamellar, columnar, cubic, and other types of phases with short-or long-range ordering were obtained [32][33][34][35][36][37].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Utilization of liquid crystals has been a promising approach . Combining the optical properties of nanoparticles with the structural adaptability of liquid crystal (LC) systems has allowed the development of switchable materials .…”
Section: Introductionmentioning
confidence: 99%
“…Covering the surface of nanoparticles with properly designed LC ligands yields systems able to form nematic, smectic, and complex 3D structures . It was shown that the melting of LC affects the plasmonic properties of the material (i.e., causes the shift of SPR wavelength), therefore significant effort was directed at controlling the organization of nanoparticles by temperature . However, obtaining fast‐reacting or remotely controlled materials require use of stimuli other than temperature.…”
Section: Introductionmentioning
confidence: 99%